Independent MBKM Internship in the Finance Department of PT. Pegadaian Kantor Wilayah XII Surabaya: Pelaksanaan Magang Mandiri MBKM di Departemen Keuangan PT. Pegadaian Kantor Wilayah XII Surabaya - Bintang Waskita Raya; Yuniningsih (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The job market today is extremely competitive. Many factors are considered by companies when selecting candidates, one of which is the competence of prospective employees. The MBKM internship program aims to provide students with broad opportunities to explore their interests and talents in the professional world. Additionally, the program helps students enhance their practical skills in their chosen fields. The internship offers numerous benefits, including both soft skills and hard skills. Students have the chance to explore their potential and gain a clearer understanding of their future career paths. The internship was conducted over a full semester, from August 5, 2024, to January 5, 2025, at PT. Pegadaian Kantor Wilayah XII Surabaya, specifically in the finance department. The data was collected through interviews, observations, documentation, literature studies, and internship reports. The results of the internship show that students improved their practical skills and adaptability for future professional environments.